Peningkatan Kesadaran Kesehatan Metabolik Melalui Edukasi dan Pemeriksaan Trigliserida pada Masyarakat Kota Bambu, Jakarta Barat - Sari Mariyati Dewi Nataprawira; Santoso, Alexander Halim; Mulyono, Alya Dwiana; Jeffrey Jeffrey (Pusat Riset dan Inovasi Nasional, 2026)
Introduction: Triglycerides are a lipids fractions that play an important role in energy metabolism, but high levels in the blood are strongly associated with increased risk of cardiovascular disease, metabolic syndrome, and type 2 diabetes. The prevalence of hypertriglyceridemia tends to increase, including in urban area such us West Jakarta which have high risk consumption patterns. This community service activity aimed to raise public awareness about the importance lipid profile management with screen triglyceride levels in community of Kelurahan Kota Bambu. Method: The activity was conducted in June 2025, involving 168 adult participants. The method was used was health education on the role of triglycerides and their risk,, followed by laboratory testing using the Nesco BL-101 5in1 Lipid Panel Monitoring System. Triglyceride level was classified into normal, borderline, high, and very high categories according to the NCEP ATP III guidelines. Results: The average triglyceride level of the participants was 181.21 mg/dL, with a range of 47–830 mg/dL. The triglyceride levels of the majority of participants were in the normal category, but the proportion with high and very high triglyceride levels was significant, indicating the existence of a risk group that needs attention. Conclusion: This activity confirms that simple triglyceride testing at the community level can be an effective step in early detection, education, and prevention